Effects of ziclague phytotherapic associated with kinesitherapy on the equine foot of children with spastic cerebral palsy - Martins, Jéssika da Silva; Golin, Marina Ortega (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Spasticity is the most common disorder of Cerebral Palsy (CP) and has the characteristics of decreased active movement, elastic hypertonia and hyperreflexia. Because of this, one of the main purposes of treatment is to decrease hypertonia. Thus, the herbal medicine Ziclague®, having an antispasmodic action, may offer a new possibility in addition to physiotherapy. Objective: Verify the effects of the application of the herbal medicine Ziclague on hypertonia of the sural triceps muscle of children with spastic CP. Methods: Ten children, between one and seven years of age, received application of Ziclague® spray on the triceps sural muscle before the physiotherapy sessions, during the period of twelve weeks. Evaluations were performed using the Modified Ashworth Scale (MAS), Durigon Protocol (DP) and goniometry, before and after application on the first day, after four weeks and at the end of twelve weeks. The four evaluations were compared. Results: After twelve weeks the results were more evident, with a decrease in hypertonia of the right lower limb (RLL) and left lower limb (LLL) verified by MAS (p= 0.06 and p= 0.13), and by the DP (p= 0.003 and p= 0.007). Goniometry showed increased range of motion for dorsiflexion of the RLL (p= 0.002) and LLL (p= 0.111). Conclusion: The use of Ziclague® associated with physiotherapy had a positive effect in decreasing hypertonia of the sural triceps muscle and in increasing the ankle dorsiflexion range of motion.